(untitled) (Research, Society and Development, 2022)
Botulinum toxin is a microbial protein, that is, a metabolite produced by the bacterium Clostridium botulinum, a protein whose mechanism of action is transient flaccid neuromuscular paralysis, having the function of relaxing the muscles, having seven different serotypes (A, B, C, D, E, F and G), which are released through the lysis of this bacterium. Type A Toxin is used in temporary aesthetic procedures, which are considered non-surgical and minimally invasive. Objective: To this end, the objective was to analyze the pharmacological action and risks of the use of Botulinum Toxin Type A in facial aesthetic procedures. Method: an integrative literature review study with the LILACS, PUBMED/MEDELINE and SCIELO databases, between 2012 and 2022. 75 articles were identified, 10 of which were used in the elaboration of the work. Results show that botulinum toxin type A over the years, has been shown to be an effective procedure both in the clinical and aesthetic areas. However, it is necessary that its application is carried out with a correct dosage, analyzing each patient, to avoid possible complications. Thus, its use has contributed to the improvement of self-image and expressive ability, generating positive social impact and better quality of life.